Propuesta de un modelo de gestión por competencias en la selección de talento humano del Gobierno Autónomo Descentralizado del cantón Chone - Bazurto Bravo, Dayana Lisbeth (2023)
Management by competencies is a model that provides different entities with strategies aimed at improving their business institutional through the selection of quality personnel. In the present investigation, a competency-based management model is proposed for the selection of human talent of the Decentralized Autonomous Government of Canton Chone during the period 2022 - 2023. Initially, the diagnosis of the current situation of human talent management of the GAD of Chone was carried out, through the analysis of its manual of functions and the application of an interview with the director of the department. Subsequently, a competency-based management model was proposed as an instrument to strengthen the selection of human talent for the Chone GAD. Finally, the results of the investigative process were socialized, in the presence of the personnel who work in the Department of Human Talent of the GAD of Chone. From the results obtained, it was determined that this public institution already has a selection process for its staff; however, they mentioned requiring a Competence Management Model that strengthens their current process and directs them towards continuous improvement. In conclusion, the importance of having a Competency Management Model lies in contemplating the development of skills required for the professional and personal progress of each employee, contributing to the continuous improvement of the organization.